A baseline analysis of marine debris on southern islands of Belize. (November 2021) - Blanke, Jayla M.; Steinberg, Michael K.; Donlevy, James P.
Abstract: Marine debris is a global issue with acute impacts. Using beach transect surveys, this study investigates debris prevalence on 7 islands in the Caribbean country of Belize. 1754 items were cataloged based on object size, form, material, condition, and economic use. Most of the litter was plastics (68.1%). Styrofoam was the second highest in abundance (9.46%), followed by foam/rubber items (8.04%), glass (3.82%), metal (2.57%), and aluminum (1.94%). Most litter was associated with an urban source (74.8%), while 4.2% and 2.1% were linked to industrial and fishing activities respectively. This study provides a novel baseline for future studies in the scarcely studied region, especially as Belize's economy continues in the conscious shift away from single-use plastic and styrofoam products. Highlights: Research provides novel data of debris prevalence on islands of southern Belize. Inverse relationship between an island's foot traffic and amount of visible debris. Large items such as plastic and glass beverage bottles were the most frequent items found. Single-use plastics and anthropogenic-related items dominate the region. An island's economic use influences the composition of marine debris present.